Study on the Temperature Field of Wet Brake Contact Interface based on Fractal Theory - Cui Tingqiong; Fan Jianwen; Zhu Enzhou; Guan Jing (Jixie chuandong)
In order to improve the braking performance and service life of wet brake,taking the wet brake of the dump truck as research object,based on the fractal theory,considering the influence of variable effect of moving heat source and friction heat flow,the mathematic model of wet brake temperature field is established,the 3D solid model of friction pair is established in the CATIA and the emergency braking is simulated by using the finite element analysis software ANSYS,the wet brake temperature field and stress field distribution are studied. The results show that the temperature and stress of wet brakes concentration in the radial edge position under emergency braking situations,this position is the most prone to thermal wear and thermal failure,it is consistent with the friction pair damage position in the process of actual use,which provides a reliable theoretical basis for the design and selection of wet brake.